Epidemiological characteristics and transmissibility of shigellosis in Hubei Province, China, 2005 – 2017 - Chen, Qi (BMC Infect Dis, 2020)
BACKGROUND: Shigellosis is one of the main diarrhea diseases in developing countries. However, the transmissibility of shigellosis remains unclear. METHODS: We used the dataset of shigellosis cases reported between January 2005 and December 2017, from Hubei Province, China. A mathematical model was developed based on the natural history and the transmission mechanism of the disease. By fitting the data using the model, transmission relative rate from person to person (b) and from reservoir to person (b(w)), and the effective reproduction number (R(eff)) were estimated. To simulate the contribution of b and b(w) during the transmission, we performed a “knock-out” simulation in four scenarios: A) b = 0 and b(w) = 0; B) b = 0; C) b(w) = 0; D) control (no intervention). RESULTS: A total of 130,770 shigellosis cases were reported in Hubei province, among which 13 cases were dead. The median annual incidence was 19.96 per 100,000 persons (range: 5.99 per 100,000 persons – 29.47 per 100,000 persons) with a decreased trend (trend χ(2) = 25,470.27, P < 0.001). The mean values of b and b(w) were 0.0898 (95% confidence interval [CI]: 0.0851–0.0946) and 1.1264 × 10(− 9) (95% CI: 4.1123 × 10(− 10)–1.8416 × 10(− 9)), respectively. The “knock-out” simulation showed that the number of cases simulated by scenario A was almost the same as scenario B, and scenario C was almost the same as scenario D. The mean value of R(eff) of shigellosis was 1.19 (95% CI: 1.13–1.25) and decreased slightly with a Linear model until it decreased to an epidemic threshold of 0.99 (95% CI: 0.65–1.34) in 2029. CONCLUSIONS: The incidence of shigellosis is still in high level. The transmissibility of the disease is low in Hubei Province. The transmission would be interrupted in the year of 2029.